2020
DOI: 10.3389/fphar.2020.510339
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Interventions to Improve Medication Adherence for Cardiovascular Diseases

Abstract: Over the past half-century, medical research on cardiovascular disease (CVD) has achieved a great deal; however, medication adherence is unsatisfactory. Nearly 50% of patients do not follow prescriptions when taking medications, which limits the ability to maximize their therapeutic effects and results in adverse clinical outcomes and high healthcare costs. Furthermore, the effects of medication adherence interventions are disappointing, and tailored interventions have been proposed as an appropriate way to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 63 publications
1
35
0
1
Order By: Relevance
“…Adherence to antiplatelet medication represents the basic requirement for successful treatment of PAD patients. Although medications used in treatment of CV diseases have improved significantly, adherence to these medications remains unsatisfactory ( Xu et al, 2020 ). The issue of medication adherence is particularly relevant in case of asymptomatic conditions (e.g., treatment of CV risk factors) ( Burnier, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to antiplatelet medication represents the basic requirement for successful treatment of PAD patients. Although medications used in treatment of CV diseases have improved significantly, adherence to these medications remains unsatisfactory ( Xu et al, 2020 ). The issue of medication adherence is particularly relevant in case of asymptomatic conditions (e.g., treatment of CV risk factors) ( Burnier, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…5,7,8,11,12 Furthermore, these articles demonstrated the benefits of having pharmacists involved to improve medication adherence via telehealth. 1,9,10 These articles studied similar populations, interventions, and telehealth methods making the comparison of this review congruent. Analyzed studies can be further reviewed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Centers of Medicare and Medicaid Services, a patient that is adherent to his/her medication(s) takes the prescribed regimen correctly at least 80% of the time. 1 Studies have demonstrated that pharmacist's involvement enhances patient adherence. 2 Telehealth allows healthcare workers to access populations in rural areas or individuals who may not have the ability to physically see a provider.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Managers of health centers can support the organization of support groups and group training, such as mindfulness or stress management. Many studies support the effectiveness of such interventions in improving medication adherence [ 28 , 58 ].…”
Section: Discussionmentioning
confidence: 99%